Revitalisasi Pendidikan Islam melalui Nilai-Nilai Tasawuf: Menggali Kearifan Spiritual di Tengah Tantangan Modernitas - A’imatul Kutbaniyah; Ririn Muktamiroh; Sal Shakhiba Albira Nanda Hanafi; Azizatur Rosyidah (Universitas Islam Lamongan, 2025)
Modernization and technological advancement bring both positive and negative impacts on human life, including spiritual crises and the loss of existential meaning. Sufism, as a spiritual legacy of Islam, offers solutions through the purification of the soul, moral cultivation, and closeness to God. This study employs a descriptive-analytical qualitative approach, utilizing literature review and an examination of contemporary phenomena to explore the relevance of Sufi values in addressing the challenges of modernity. The findings indicate that the revitalization of Sufism can serve as a paradigm in Islamic educational praxis. Core values such as tazkiyat al-nafs (self-purification), tawakkal (trust in God), ṣabr (patience), zuhd (asceticism), and universal compassion are highly relevant for application in Islamic education to shape a generation with strong character, tolerance, and divine consciousness. This revitalization responds to the demands of the contemporary era and holds the potential to become a transformative force in building a humanistic and civilized society.